2005
DOI: 10.1097/01.hjh.0000160203.35910.9f
|View full text |Cite
|
Sign up to set email alerts
|

Results of blood pressure screening in a population of school-aged children in the province of Milan: role of overweight

Abstract: Our study indicates the importance of performing BP screenings in the paediatric population, and to promote interventions that may reduce the prevalence of OW in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 25 publications
11
91
1
6
Order By: Relevance
“…Previous studies have shown that obesityis closely associated with blood pressure 8,49 and hypertension in adults 50 as well as in children and adolescents. [13][14][15][16] Studies have also shown that elevated HR is an important predictor of death and is caused by mainly by cardiovascular diseases. Resting tachycardia has been linked to the development of atherosclerosis and cardiovascular events in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that obesityis closely associated with blood pressure 8,49 and hypertension in adults 50 as well as in children and adolescents. [13][14][15][16] Studies have also shown that elevated HR is an important predictor of death and is caused by mainly by cardiovascular diseases. Resting tachycardia has been linked to the development of atherosclerosis and cardiovascular events in adults.…”
Section: Discussionmentioning
confidence: 99%
“…11 According to cutoffs suggested by the World Health Organization, individuals with BMI o18.50 kg m À2 are underweight, with BMI 18.50-24.90 kg m À2 are normal, with BMI of 25-29.90 kg m À2 are considered overweight and with BMI of X30 kg m À2 are considered as obese. 12 Previous studies have shown that obesity is associated with cardiovascular abnormalities, such as hypertension [13][14][15][16][17][18] and high resting heart rate (HR). 19,20 Hypertension is a strong predictor of cardiovascular diseases and death 21,22 and is also an important component of the metabolic syndrome, 23 which is a risk factor for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, it is not simple to define and to quantify each item, and some suggested risk criteria reference standards are still missing, but this pathway could help pediatricians to decide which subjects to evaluate and follow-up in depth. In this scenario, we consider hypertension, recently confirmed a frequent finding in childhood obesity, [95][96] as a clinical feature because of its possibility to be assessed during a standard clinical examination.…”
Section: Minor Concernsmentioning
confidence: 99%
“…15,16 Since childhood hypertension is associated with adulthood hypertension and other chronic diseases, 4 previous studies advocate the early detection and prevention of childhood hypertension. 11,15,[17][18][19] In Taiwan, the increasing availability of high fat, high calorie foods has contributed to the continually increasing obesity levels of adults and children. 20 However, no population-based studies examine the relationship between hypertension and obesity in children.…”
Section: Introductionmentioning
confidence: 99%